PREVALENCE OF COMMON MENTAL DISORDERS AND ASSOCIATED COMORBID CONDITIONS IN AN URBAN SLUM OF INDORE, M.P – A CROSS-SECTIONAL STUDY - UPADHYAY, RITESH; JAIN, VIPIN; JAIN, MEGHA; DANDOTIYA, DILEEP; SONI, RUCHI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Introduction: Epidemiology plays an important role in providing interpretation of disease occurrence in populations, change of disease rate, and the associated factors related to occurrence. Physical health problems not only coexist with mental disorders such as depression, but can also predict the onset and persistence of depression. A study of a nationally representative sample of the United States showed 79% of all ill people were comorbid. Aims and Objectives: The aims of this study were to study the comorbid condition in subjects with common mental disorders (CMD). Methods: It was a community-based and cross-sectional study carried out in an urban Slum. Slum was divided into four quadrants and 10% of the population was taken. A total of 150 houses were visited by random sampling and the sample size was calculated to be 294. The study was recorded in a pilot tested pre-designed validated semi-structured questionnaire. Four hundred and twenty-three out of 467 people were included in the study which was conducted in two phases. First phase was the screening phase which included history, general examination, and demographic profile along with self-reporting questionnaire (SRQ-20) to measure the presence of mental illness. Socioeconomic status of family and quality of life was evaluated using Kuppuswami socioeconomic status scale. Subjects scored 7 and above selected for the study and further evaluated using mini international neuropsychiatric interview plus in the second phase. Results: In the present study, highest percentage of CMD was 26.47%, belonging to 16–25 age group and distress was found in 16.07% and severe distress in 7.80% with SRQ-20 scoring between 7 and 13 and >14, respectively, with higher proportion of females. The prevalence of CMD was 238.77/1000 and 11.88% and 8.91% subjects were found hypertensive and diabetic respectively. Conclusion: There is need to consider the impact of common psychological health problems that urban slum communities are facing today and CMD can be a major contributor to slum’s overall burden of functional impairment.